Aplikasi Marketplace Penyewaan Mobil Berbasis Website menggunakan Metode Rapid Application Development - Arfando Saputra; Fajar Ratnawati; Elvi Rahmi (Repeater : Publikasi Teknik Informatika dan Jaringan, 2024)
Marketplace system is a means of meeting sellers and buyers online, in this case service providers and car renters. With this information system, renters no longer need to bother looking for the required car that matches the criteria, and service providers are also easier in marketing and expanding their marketing reach. This system was built using the RAD (Rapid Application Development) method of development which allows customers to place orders, select vehicles, eliminating complexity in the traditional process involving visits to rentals. In car rental services there are several problems that need to be resolved. First, there is no web-based information system service that makes it easy for customers to access car rental service company information. Second, conventional services are still fairly slow. Currently, reservations are made in two ways, namely coming to the place or contacting the telephone number on Whatsapp so that prospective tenants have to wait for a response from the rental provider to get information about prices and available cars. Therefore, a car rental information system is needed that specifically serves fleet rental with online booking to display transaction information in the form of car rental and return on the system dashboard to support strategic purposes. This research focuses on building a car rental information system using the PHP programming language with the CodeIgniter framework.